2021
DOI: 10.1016/j.isci.2021.102795
|View full text |Cite
|
Sign up to set email alerts
|

3D single cell scale anatomical map of sex-dependent variability of the rat intrinsic cardiac nervous system

Abstract: Highlights3D anatomical map of rat intrinsic cardiac nervous system Preferential organization of neurons in select cardiac anatomical regions Conserved anatomical organization of intrinsic cardiac neurons across sexesGeneralized 3D scaffold for mapping of highresolution cardiac anatomical data

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Having these types of information on a scaffold contributes to a more thorough understanding of the organ innervation, as well as making the data more accessible and replicable for other scientists. This is a joint effort from multiple researchers to not only produce the data, but also use the data to navigate 2D connectivity maps and build 3D organ scaffolds that can provide a comprehensive brain‐organ atlas and “a common coordinate framework for cross‐species comparisons” (Achanta et al., 2020; Leung et al., 2021; Osanlouy et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Having these types of information on a scaffold contributes to a more thorough understanding of the organ innervation, as well as making the data more accessible and replicable for other scientists. This is a joint effort from multiple researchers to not only produce the data, but also use the data to navigate 2D connectivity maps and build 3D organ scaffolds that can provide a comprehensive brain‐organ atlas and “a common coordinate framework for cross‐species comparisons” (Achanta et al., 2020; Leung et al., 2021; Osanlouy et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, a recent study (Leung et al, 2021) explored sex differences in the rat intrinsic cardiac nervous system, which includes the network of the intracardiac ganglia and interconnecting neurons that receive inputs from both local afferent and extrinsic autonomic (vagal and sympathetic) nerves (Achanta et al, 2020). The authors found that female rat hearts had fewer neurons and lower packing density than males, which may explain some of the sex differences observed at a functional level (Leung et al, 2021). Given such findings and the current results, we believe that rat models offer an important opportunity to systematically investigate the neuro-hormonal basis of the sex difference in the relationship between vmHRV and cardiac chronotropy.…”
Section: Implications For Translational Researchmentioning
confidence: 95%
“…Further, studies in rats have shown that i) vagal nerve stimulation leads to greater cardiac effects in female than male rats, presumably due to a higher level of ACh release following nerve activation (Du et al, 1994), that ii) the enzymatic breakdown of ACh occurs slower in newborn female than male rats (Loy and Sheldon, 1987), and that iii) the synthesis and clearance of neurotransmitters, including ACh, in both the heart and vasculature are regulated by sex hormones (Dart et al, 2002). Intriguingly, a recent study (Leung et al, 2021) explored sex differences in the rat intrinsic cardiac nervous system, which includes the network of the intracardiac ganglia and interconnecting neurons that receive inputs from both local afferent and extrinsic autonomic (vagal and sympathetic) nerves (Achanta et al, 2020). The authors found that female rat hearts had fewer neurons and lower packing density than males, which may explain some of the sex differences observed at a functional level (Leung et al, 2021).…”
Section: Implications For Translational Researchmentioning
confidence: 99%
“…Such studies have investigated neurocardiac interactions using an aspect ratio where the cardiomyocytes outnumber neuronal cells, demonstrating a functional and viable co-culture [7,11,12]. Although the distribution and numbers present in cardiac tissue have not been extensively studied, intrinsic cardiac neurons are distributed in a similar pattern and form a limited number of clusters within the cardiac tissue [13].…”
Section: Introductionmentioning
confidence: 99%
“…By incorporating multiple arrowheads into the design, the scaffold design was intended to replicate the geometry and morphology of myocardial tissue [6], and adding an even layer with neuronal cells potentially mimicked the organization of a CANS model [13]. It was expected that this design would promote effective networking between neurons and cardiomyocytes in comparison with a 2D platform [7].…”
Section: Introductionmentioning
confidence: 99%